ANALISIS HUBUNGAN TINGKAT PEMAHAMAN MATERI PERKULIAHAN PENGANTAR ILMU LINGKUNGAN DENGAN MENGGUNAKAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR MAHASISWA - Vina N Van Harling (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Google classroom is a service developed by Google, in this case, Google for Education, which aims to simplify the assignments of teachers. This research was conducted to analyze the relationship between the level of understanding of environmental science introductory course material using google classroom on student learning outcomes. This research is a correlational study, the research data were collected using a questionnaire collection method and documentation method. The research was conducted at Saint Paul Polytechnic in Sorong, an Electrical Engineering study program, the sample used was 9 people from the total population. The test results obtained by r count from the results of testing the relationship between the level of understanding of introductory environmental science subject matter using Google Classroom to student learning outcomes of 0.158 which when compared to the test results with the value of r table, then the value of r count <r table (0.158 <0.666). While the comparison of significance obtained a significance value> 0.05 (0.686> 0.05), which means that there is no relationship between the two variables tested.